Regular relations and hyperideals in Hv-γ-semigroups - Hedayati H.; Davvaz B. (Utilitas Mathematica, 2011)
In this paper, the concept of an Hv-γ-semigroup is introduced. Then, the regular equivalence relations on Hu-γ- semigroups and their properties are investigated. Specially, it is shown that homomorphisms of Hu-γ-semigroups cam induce regular equivalence relations. Finally, by using the notion of regular relation on H u-γ-semigroups an isomorphism theorem is proved.